Composing research : a contextualist paradigm for rhetoric and composition - Johanek, Cindy, 1964- (Utah State University Press, 2000)
In Composing Research, Cindy Johanek offers a new perspective on the ideological conflict between qualitative and quantitative research approaches, and the theories of knowledge that inform them. With a paradigm that is sensitive to the context of one's research questions, she argues, scholars can develop less dichotomous forms that invoke the strengths of both research traditions.